2022
DOI: 10.1167/iovs.63.11.20
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Diurnal Rhythms of the Human Eye: Implications for Continuing Ocular Growth in Adolescents and Young Adults

Abstract: Purpose To investigate the diurnal rhythms in the human eye in winter and summer in southeast Norway (latitude 60°N). Methods Eight measures (epochs) of intraocular pressure, ocular biometry, and optical coherence tomography were obtained from healthy participants (17–24 years of age) on a mid-winter's day ( n = 35; 6 hours of daylight at solstice) and on a day the following summer ( n = 24; 18 hours of daylight at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 93 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…In a review of the repeatability of autorefraction, the mean estimated 95% LoA for repeatability of cycloplegic SER was ±0.41 D 28 . Although SER is an important clinical measurement, most autorefractors do not have comparable accuracy to that of ocular biometers, except perhaps the HRK‐8000A with a reported repeatability of ±0.056 D (95% CI 0.052, 0.061) 20 . Compared with the HRK‐8000A, the Myopia Master measured on average 0.19 D more minus SER, but no differences on average for J 0 and J 45 (Table 2, Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a review of the repeatability of autorefraction, the mean estimated 95% LoA for repeatability of cycloplegic SER was ±0.41 D 28 . Although SER is an important clinical measurement, most autorefractors do not have comparable accuracy to that of ocular biometers, except perhaps the HRK‐8000A with a reported repeatability of ±0.056 D (95% CI 0.052, 0.061) 20 . Compared with the HRK‐8000A, the Myopia Master measured on average 0.19 D more minus SER, but no differences on average for J 0 and J 45 (Table 2, Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The autorefraction values reported by the instrument are the mean of five measurements obtained with a minimum pupil diameter of 2.0 mm. The instrument has been reported to have high measurement repeatability 20 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The children viewed a large letter or another suitable non-accommodative object at a distance of at least 6 metres. Non-cycloplegic and cycloplegic autorefraction were performed utilising the Huvitz HRK-8000A Auto-REF Keratometer (Huvitz Co. Ltd., Gyeonggi-do, Korea), which has been shown to have high repeatability (Nilsen et al, 2022). Results from autorefraction were automatically calculated from five measurements.…”
Section: Methodsmentioning
confidence: 99%
“…A Norwegian study found significantly higher degrees of hyperopia (0.5 D) after cycloplegia (cyclopentolate 1%) in children aged 10-15 years (Thorud et al, 2021). Some studies have found good inter-and intra-repeatability of cycloplegic retinoscopy in children for experienced clinicians (Hirsch, 1956;McCullough et al, 2017), although cycloplegic autorefraction typically gives higher repeatability than cycloplegic retinoscopy (Fotouhi et al, 2012;Nilsen et al, 2022;Sankaridurg et al, 2017;Zadnik et al, 1992). Clinical studies show considerable between-individual variation when noncycloplegic and cycloplegic refraction methods are compared (L. B.…”
Section: Introductionmentioning
confidence: 99%